2009
DOI: 10.1002/cjg2.1341
|View full text |Cite
|
Sign up to set email alerts
|

Modeling on Gas Hydrate Formation Conditions in the Qinghai‐Tibet Plateau Permafrost

Abstract: Based on the field‐investigated gas geochemistry, the modeling of gas hydrate formation conditions is conducted in the Qinghai‐Tibet plateau permafrost (QTPP) in combination with predecessors' data such as the permafrost ground temperature (T0), the thermal gradient within the frozen layer (G1) and the thermal gradient below the frozen layer (G2). The modeled results show that the permafrost characteristics generally meet the requirements for gas hydrate formation conditions in the study area. Gas composition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…The basic parameters of T0, G1 and G2 shown in Table 1 are determined based on field measurements [7,8]. Then the initial temperature and pressure at the bottom of the HBL (TB and PB) are initialized to be 277.84 K and 4.19 MPa, respectively (Table 1).…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic parameters of T0, G1 and G2 shown in Table 1 are determined based on field measurements [7,8]. Then the initial temperature and pressure at the bottom of the HBL (TB and PB) are initialized to be 277.84 K and 4.19 MPa, respectively (Table 1).…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
“…Previous studies indicated that the annual average of the permafrost ground temperature (T0) was around −1 to −3 °C. Based on in situ measurements in this area, the geothermal gradients within and below the frozen layers (G1 and G2) of the QTPP were approximately in the range of 0.011-0.033 °C/m and 0.028-0.051 °C/m, respectively [7,8]. These thermodynamic conditions are favorable for the formation of natural gas hydrate in the Qilian Mountain.…”
Section: Introductionmentioning
confidence: 99%
“…The physical parameters (T 0 , G 1 and G 2 ) come from the field measurements (Lu et al, 2009;Wu et al, 2010), as shown in Table 1. Then the temperature at the bottom of the HBL (T B ) is initialized to be 277.84 K ( Table 1).…”
Section: Initial Conditionsmentioning
confidence: 99%
“…where ρ r is the rock density of the permafrost layer (2000 kg/m 3 ) (Lu et al, 2009), ρ w is the fluid density under the permafrost layer (l000 kg/m 3 ), g is the gravitational acceleration (9.81 m/s 2 ), and P 0 is the atmospheric pressure (1.01 × 10 5 Pa). Eq.…”
Section: Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation